EXPLORING UNIVERSITY STUDENTS’ ATTITUDES TOWARDS THEIR ENGLISH ACCENT AND NATIVE ENGLISH ACCENTS - Mia Rahmawati Yuwita; Nisrina Dewi Ambarwati (Linguistics and Literature Students' Journal, 2023)
This current study examines university students’ attitudes towards their English accents and native English accents. Over the past few decades, the study of attitudes towards English accents has gained considerable attention owing to its multifaceted nature within the context of second language acquisition. The examination of such attitudes is known to be thought-provoking due to its entanglement with sociocultural, sociohistorical, language contact, and language learning experience factors. To achieve the study's objectives successfully, a semi-structured interview was conducted to gather rich and authentic data. The participants of the study, comprising first-year and third-year English literature students, were interviewed to elicit their views on English accents. The findings of the study reveal the presence of both positive and negative attitudes towards the participants' English accents, with a prevailing belief that so-called native English accents carry greater prestige than others. The implications of these findings have enriched the fields of applied linguistics and provide insights into future English Language Teaching, particularly from the English as an International Language perspective. Keywords: English, English accent, language attitude, university students